School supportiveness and innovative abilities in vocational education: the mediating role of motivation to innovate among vocational teachers - Fongkanta, Pongwat; Buakanok, Fisik Sean (Frontiers in Education, 2025)
Creativity and innovation have become essential elements for vocational teachers to drive advancements in education. This study aimed to explore the innovative capabilities of vocational teachers and compare these abilities across the different levels of classes they teach. Furthermore, a causal model of innovative educational capabilities (IEC) was developed and validated to investigate the innovation that vocational teachers in Northern Thailand can employ. We utilized data from a cross-sectional survey of 560 vocational teachers to estimate and validate the causal model using Analysis of Moment Structures (AMOS). The results revealed that the overall innovative capability levels were high. There were statistically significant differences in innovative capabilities across class levels of teaching. Ultimately, the causal model demonstrated a good fit to the data and showed that motivation to innovate can mediate the relationship between school supportiveness (SCS) and innovative educational capabilities.